Distribution and contamination of trace elements in mangrove sediments collected from West Coast of Peninsular Malaysia - Krishnan, Kumar; Saion, Elias; Chee, Kong Yap; AS, Nadia (Horizon Research Publishing, 2022)
In tropical and subtropical latitudes, woody plants known as mangroves flourish in slimy, anaerobic soils on the boundary between land and sea. They can withstand extreme weather conditions like high temperatures, unreliable tides, strong winds, and salt. The objective of this study was to determine the concentration of nine trace elements (Hf, Ga, Ba, V, Cs, Sc, Sb, Ta, and Co) in the sediment of the mangrove forest along the west coast of Peninsular Malaysia. Instrumental neutron activation analysis (INAA) was employed to determine the distribution of the elements within the sediments. The concentration of trace elements in the sediment in descending order are Sb < Co < Ta < Sc < Hf < Cs < Ga < V < Ba. The degree of elemental contamination in the sediments was assessed using the enrichment factor (EF) and geoaccumulation index (Igeo). The EF and Igeo of trace element ranged from 0.41 to 20.76 and -3.56 to 1.41 respectively. The EF and Igeo values of a few trace elements in the sediments at Kampung Panchor (L6) suggested that the area had probably deteriorated.